Incidence of primary graft dysfunction after lung transplantation is altered by timing of allograft implantation. Issue 4 (9th October 2018) - Cunningham, Peter S; Maidstone, Robert; Durrington, Hannah J; Venkateswaran, Rajamayier V; Cypel, Marcelo; Keshavjee, Shaf; Gibbs, Julie E; Loudon, Andrew S; Chow, Chung-Wai; Ray, David W; Blaikley, John F
Abstract : The importance of circadian factors in managing patients is poorly understood. We present two retrospective cohort studies showing that lungs reperfused between 4 and 8 AM have a higher incidence (OR 1.12; 95% CI 1.03 to 1.21; p=0.01) of primary graft dysfunction (PGD) in the first 72 hours after transplantation. Cooling of the donor lung, occurring during organ preservation, shifts the donor circadian clock causing desynchrony with the recipient. The clock protein REV-ERBα directly regulates PGD biomarkers explaining this circadian regulation while also allowing them to be manipulated with synthetic REV-ERB ligands.